Autonomia em Kant: pela crítica da crítica científica - PINTO SERRÃO, Daniel; BORGES MENESES, Ramiro Delio (Revista de Filosofía, 2010)
This paper tries to synthesize the a priori foundations of Kant’s autonomy principle, deciphering its sense and epistemic value, from the Critique of Practical Reason to the Foundations of Metaphysics of Customs.
Keywords: Kant; Autonomy; Criticism; Metaphysics; Casuistic; Neurosciences